On the Advantage of Being the First Server - Hassin, Refael (Management Science, 1996)
The following example illustrates the problem treated in this paper: Two gas stations are located one after the other on a main road. A driver who needs to fill his rank sees the queue situation at the first station but not at the second one. The driver estimates the expected waiting time at the first station, compares it to the conditional expected waiting time at the second one, and decides which station to enter. The second station is assumed to be on the driver's route so that no extra cost is involved in choosing it. Is it true that the first station always gets a higher share of the demand than the second one? We model the situation in terms of queueing theory and answer the question.